Innovation and productivity: empirical evidence for Brazilian industrial enterprises - Luciana Carvalho; Ana Paula Macedo de Avellar (RAUSP: Revista de Administração da Universidade de São Paulo)
Abstract The aim of this paper is to carry out an empirical investigation into the relationship between innovation and the productive performance of Brazilian businesses measured by Work Productivity and Total Factor Productivity. Data taken from the Research of Innovation and estimated cross section models and panel data was used. The results suggest that innovation produces an incipient impact on competition in the national industry, reflected in the small magnitude of coefficients associated with the diverse indicators of innovation.